(untitled) (CIPEEX, 2025)
Introduction: Ecosystem health constitutes a relatively recent theoretical-methodological approach and has gained increasing prominence in research involving health and the environment over the past few years. Objective: This article aims to present and discuss, based on a bibliographic literature review, a current overview of ecosystem health, as well as other emerging approaches associated with the topic. Methods: A bibliographic search was conducted in databases regarding the proposed topic: ecosystem health as an approach in health studies. Results: In Brazil and regarding the “value of the environment,” issues such as education, health, housing, and other topics related to the quality of life and collective well-being of the population are far from an optimal effectiveness panel. Ecosystem thinking introduces a new discipline called ecosystem health, which seeks to identify ecosystem management strategies for the participatory construction of integrated solutions that promote improvements in health and living conditions. Concepts and updates in this field aim to explain the terms Earth health, topophilia, biophilia, and symbiocene. Ecosystem health and mental health seek to understand, in the scientific literature, disorders such as depression and anxiety and their correlations with the environment. Environmental gerontology is conceived as the field dedicated to describing, explaining, and optimizing the relationship between older adults and their socio-spatial surroundings. Conclusion: It is expected that this brief discussion contributes to the dissemination of knowledge about some theoretical foundations of ecosystem health and its new perspectives.